Possibilities for the determination of acids of fats and vegetable oils by indirect complexometry with Pb (II) and establishment of a new index in them called "Complexometric". II.- Determination of olive, soy, peanut, sunflower and cotton oils - López Martínez, Mª.C.; García Villanova, R. (Ars Pharmaceutica (Internet), 1968)
A new method is proposed for determination of olive, soy bean, sunflower peanut and cottonseed oils, after their saponification with KOH solution, precipitating with a excess of standard solution of Pb (II) and titration in the filtrate with EDTA solution of identifical molarity, using Eriochrome Black T as indicator. The errors found are small in olive, peanut and cottonseed oils, while those in soy bean oil are from 2.37 to 5.17% and in sunflower oil from 3.0 to 5.30% in the ten samples of each vegetable oil assayed.